การพัฒนาและการใช้ชุดกิจกรรมศิลปะเพื่อส่งเสริมความคิดสร้างสรรค์ของนักเรียนชั้นประถมศึกษาปีที่ 4 - กรรณิกา, ปรียาภรณ์; เครือคำอ้าย, วชิรา; ภู่วิภาดาวรรธน, ผจงกาญจน์ (Ganesha Journal, 2015)
งานวิจัยนี้มีวัตถุประสงค์เพื่อพัฒนาและหาประสิทธิภาพของชุดกิจกรรมศิลปะเพื่อส่งเสริมความคิดสร้างสรรค์ เปรียบเทียบผลคะแนนความคิดสร้างสรรค์ของนักเรียนก่อนและหลังการเรียนด้วยชุดกิจกรรม รวมถึงสังเกตพฤติกรรมที่แสดงออกถึงลักษณะของผู้ที่มีความคิดสร้างสรรค์ ประชากรที่ใช้ในการวิจัยครั้งนี้ คือ นักเรียนชั้นประถมศึกษาปีที่ 4 โรงเรียนวัดปางเติม จำนวน 13 คน เครื่องมือที่ใช้ในการวิจัย ได้แก่ ชุดกิจกรรมศิลปะเพื่อส่งเสริมความคิดสร้างสรรค์ แบบวัดความคิดสร้างสรรค์ และแบบสังเกตพฤติกรรมที่แสดงออกถึงลักษณะของผู้ที่มีความคิดสร้างสรรค์ วิเคราะห์ข้อมูลทางสถิติด้วย ค่าความถี่ ค่าร้อยละ ค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน การหาประสิทธิภาพชุดกิจกรรม และทดสอบสมมุติฐานโดยหาค่าดัชนีประสิทธิผล ผลการวิจัยพบว่า ได้ชุดกิจกรรมศิลปะเพื่อส่งเสริมความคิดสร้างสรรค์ จำนวน 5 ชุดกิจกรรมที่มีประสิทธิภาพเท่ากับ 77.57/80.44 และหลังการเรียนนักเรียนมีความคิดสร้างสรรค์เพิ่มขึ้น 0.61 หรือ คิดเป็นร้อยละ 61 พฤติกรรมที่แสดงออกถึงลักษณะของผู้ที่มีความคิดสร้างสรรค์ มากที่สุด 3 อันดับ คือ ความสนุกสนานร่าเริง ความช่างสังเกต การถามคำถามที่แปลกใหม่น่าสนใจ และพฤติกรรมที่แสดงออกน้อยที่สุด คือ กล้าพูด DEVELOPMENT AND IMPLEMENTATION OF USING ART ACTIVITY PACKAGES FOR CREATIVE THINKING OF PRATHOM SUKSA 4 STUDENTS The purposes of this research were to develop art activity packages for creative thinking development of Prathom Suksa 4 students, to study their effectiveness by using criteria of effectiveness with a proportion of 75/75, to compare student’s scores of creative thinking before and after using art activity packages, and to observe students’ creative thinking behavior. The population of this study was 13 students from Prathom Suksa 4 level at Wat Pang Theam School. The tools for data collection were art activity packages for developing creative thinking, a creative thinking test, and a students’ creative thinking behavior observation form. The data were analyzed for frequency, percentage, mean, and standard deviation. An effectiveness of the art activity packages could be calculated by using formula E1/E2 and hypothesis testing by using the formula of Effectiveness Index: E.I. The results of this research were the art activity packages, consisting of 5 subpackages, the art activity packages were effective at 77.57/80.44, scores of students’ creative thinking after using art activity packages increased by at 0.61 scores or 61 per cent, and the most three creative thinking behaviors that were exhibited by students during performing art activities were enjoyment and liveliness, observantness, and questioning interesting questions. The less creative thinking behavior was self-confidence to talk.